The KEPEMIMPINAN DALAM TIM DI LINGKUP ORGANISASI KAMPUS - kania, Raden; Gemilang, Raysan Duta (Jurnal Manajemen Retail, 2023)
Leadership within a team plays a key role in achieving campus organizational goals. This study investigates the dynamics of leadership in the context of campus organizations, focusing on its influence on team performance and achieving shared goals. This research uses a qualitative approach with in-depth interviews and participant observation of team leaders and team members in the campus environment. The research results show that a participative leadership style and a deep understanding of the needs and potential of individuals in the team encourage effective collaboration. Additionally, open and clear communication from team leaders creates an inclusive work environment and supports innovation. These factors positively influence team member motivation and overall productivity. However, challenges also arise, including role uncertainty, differences in views, and conflict management. Therefore, this research recommends the importance of developing interpersonal leadership skills, conflict management, and effective communication for team leaders in the campus environment. In conclusion, leadership in teams has a significant impact on the achievements of campus organizations and requires a holistic approach to increase cooperation and achieve common goals.